Covalent organic frameworks: From materials design to electrochemical energy storage applications. Issue 2 (11th July 2021) - Lin, Jiamin; Zhong, Yiren; Tang, Lingyu; Wang, Liuqi; Yang, Mei; Xia, Hui
Abstract: Covalent organic frameworks (COFs), with large surface area, tunable porosity, and lightweight, have gained increasing attention in the electrochemical energy storage realms. In recent years, the development of high‐performance COF‐based electrodes has, in turn, inspired the innovation of synthetic methods, selection of linkages, and design of the topological structures. This review aims to present an overview of the recent advances in designing COF materials for various energy storage technologies. The fundamentals of COF materials, including synthetic chemistry, linkage diversity, and structure design, are first introduced. An in‐depth understanding of the charge storage mechanism and the structure‐property relationships of the COF electrodes is subsequently provided, highlighting their designing strategies in the latest energy storage applications. The last section of this review discusses the challenges COFs are facing and outlines new directions that could advance COF research in emerging energy technologies. Abstract : Covalent organic frameworks (COFs) with tunable porosity, composition, and structure and their recent progresses in the energy storage applications are reviewed. The fundamentals, including synthetic method, linkages selection, and structural control, are introduced, followed by an overview of the mechanistic understanding of the structure–property relations, highlighting the designing principles in different application scenarios.